Синдром "порожнього" турецького сідла - Кирилюк, М. Л. (Clinical Endocrinology and Endocrine Surgery, 2012)
The article presents the modern views on etiology, pathogenesis, clinical presentation, treatment guidelines of syndrome "empty" sella turcica.